(untitled) (The Review of Diabetic Studies, 2024)
Background: Needlestick injuries (NSIs) are one of the most common health hazards facing healthcare workers (HCWs) worldwide. Objectives: The aims of this study were to assessment the prevalence of occupational exposure to NSIs among laboratory health care working at Makkah hospital, Saudi Arabia. Also, to identify the risk factors associated with NSIs and HBV vaccination status. Method: A descriptive cross-sectional study was conducted among laboratory personnel in the health laboratory in Makkah. Data collection was done using a pretested administered questionnaire. Results: A total of 33 (34.4%) participants had been exposed to needlestick injuries during their work in the laboratory. Only 33.3% of needlestick injuries were reported to administrator in the laboratory. The prevalence rate of needlestick injury was significantly higher (65.6%) among those who had an experience of less than 5 years (P< 0.05) and those who had not (41.9%) received training course on biosafety (P< 0.05). About one-third (32.3%) of participants reported that they had been vaccinated against HBV. The vaccination coverage rate against HBV was significantly higher among laboratory personnel who had received a bachelor’s degree (P< 0.05), and those who received biosafety training course (P< 0.05). Conclusions : This study showed relatively higher prevalence rate of NSIs among the laboratory health care worker. The rate of non-reported NSIs is also high among laboratory personnel who had needlestick injuries. Low rate of receiving biosafety training courses and low vaccination coverage among laboratory personnel. Therefore, laboratory personnel should be trained on safety measures for handling and disposing of needles and should be encouraged to report NSIs to get the right treatment and counseling. Also, the laboratory should be provided with protective equipment in sufficient quantities to reduce the incidence of NSIs and HBV vaccination should be achieved for laboratory personnel working at the health laboratory in Makkah.